Nest characteristics, distribution, and preferences of Megapodius reinwardt as the basis for its conservation on Lombok Island, West Nusa Tenggara, Indonesia - M. YAMIN; A. WAHAB JUFRI; ALIFMAN HAKIM; GUNAWAN GUNAWAN; JONI RAHMAT; A.A. SUKARSO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yamin M, Jufri AW, Hakim A, Gunawan, Rahmat J, Sukarso AA. 2024. Nest characteristics, distribution, and preferences of Megapodius reinwardt as the basis for its conservation on Lombok Island, West Nusa Tenggara, Indonesia. Biodiversitas 25: 1920-1928. Megapodius reinwardt Dumont, 1823 is a unique bird that has an important ecological role as an insect controller, food security, and economy. This study aims to accurately determine the distribution, characteristics of nests and nesting preferences of M. reinwardt in natural habitats. Data collection was carried out by field observation methods at three locations from March to August 2023, i.e.: TWA Gunung Tunak (Gunung Tunak Nature Park), TWA Kerandangan (Kerandangan Nature Park), and Gili Trawangan, but when data were collected on Gili Trawangan no active nests were found. We found that there are seven active nests in the western part of the TWA Gunung Tunak; each nest was built by five to twelve pairs of parents, while in TWA Kerandangan, three active nests were built by three pairs of parents. The population of M. reinwardt on Lombok Island is only found in TWA Gunung Tunak (96 heads) and TWA Kerandangan (12 heads). The presence of the nest is simultaneously significantly influenced by 14 factors (R2 value=87%). Six factors are highly preferred, i.e., distance to river streams, light intensity, canopy cover, vegetation density, humidity, and plant litter composition. The vegetation diversity in TWA Gunung Tunak was 21 species with a density of 58 - 344 individuals/hectare compared to TWA Kerandangan, which was 40 species with a density of 185-410 individuals/hectare. The diversity index (H) of M. reinwardt is between 2.14-2.26. The evenness index (E) is between 0.95-0.96. The high ecological index indicates that conservation strategies for M. reinwardt should be implemented by providing ecosystem services through the development of ecotourism and by increasing economic and community awareness.